2021
DOI: 10.3389/fpubh.2021.708965
|View full text |Cite
|
Sign up to set email alerts
|

Gender Differences in Anxiety Among COVID-19 Inpatients Under Isolation: A Questionnaire Survey During the First and Second Waves of the COVID-19 Pandemic in Japan

Abstract: This study assesses the gender differences in health and anxiety, especially pertaining to mental health problems and time-course effects. We surveyed 121 patients admitted to a hospital with a COVID-19 diagnosis between March 1 and August 31, 2020. Their mental status was evaluated on admission using the Japanese General Health Questionnaire-28 (GHQ-28) and State–Trait Anxiety Inventory—Form JYZ (STAI). The patients were divided into two groups depending on the period of prevalence, that is, the first and sec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 17 publications
3
12
0
Order By: Relevance
“…In fact, the first predictor of females is Anxious arousal of the PTSD scale, which seems to play a significant role in exacerbating the Fear of COVID-19; this dimension is also found in the male group, but with a significantly lower incidence. This finding seems to be consistent with the literature on the issue, which shows that women have higher levels of anxiety regarding the COVID-19 pandemic [ 43 , 59 , 60 , 61 ]. On the other hand, for men, the factor that most explains the investigated dependant variable (i.e., fear of COVID-19) is negative effect as measured by the PTSD scale; this finding is in contrast to the previous study by Fenollar-Cortés et al [ 44 ], in which it emerges that women have significantly higher scores than men with respect to the variable negative affect.…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…In fact, the first predictor of females is Anxious arousal of the PTSD scale, which seems to play a significant role in exacerbating the Fear of COVID-19; this dimension is also found in the male group, but with a significantly lower incidence. This finding seems to be consistent with the literature on the issue, which shows that women have higher levels of anxiety regarding the COVID-19 pandemic [ 43 , 59 , 60 , 61 ]. On the other hand, for men, the factor that most explains the investigated dependant variable (i.e., fear of COVID-19) is negative effect as measured by the PTSD scale; this finding is in contrast to the previous study by Fenollar-Cortés et al [ 44 ], in which it emerges that women have significantly higher scores than men with respect to the variable negative affect.…”
Section: Discussionsupporting
confidence: 92%
“…These data are concordant with the scientific literature present for both the general population [ 13 , 76 , 77 , 78 , 79 , 80 ] and the specific volunteer population [ 75 ], in which women show higher levels of depression, anxiety, and somatisation symptoms; however, these differences are small, probably because of the period of data collection (the second pandemic wave). In fact, some studies found that gender differences in psychological well-being faded as time went by [ 43 , 44 ]; we can imagine that these differences were slowly fading, and future studies may investigate if these differences will be still present at the end of the pandemic situation.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The purpose of this study was to investigate the attributes that influenced psychological distress in COVID-19 patients (hereafter referred to as infected patients) who were isolated in residential treatment facilities and consulted at a mental health welfare center. Because previous studies have reported higher anxiety in women than in men among patients with COVID-19 who were admitted to a medical facility for treatment [ 12 , 13 , 14 , 15 , 16 ], we hypothesized that being female would have an exacerbating effect on psychological distress. Furthermore, given that younger age groups were more anxious under urban lockdowns in overseas reports [ 1 , 2 , 17 , 18 ], we postulated a second hypothesis: that being younger than 40 years old would have had an exacerbating effect on psychological distress.…”
Section: Introductionmentioning
confidence: 99%